Pattern of Macular Ganglion Cell-Inner Plexiform Layer Defect Generated by Spectral-Domain OCT in Glaucoma Patients and Normal Subjects. Issue 8 (October 2015) - Jeong, Jae Seung; Kang, Min Gu; Kim, Chan Yun; Kim, Na Rae
<x xml:space="preserve">Abstract</x> Purpose: To elucidate patterns of macular ganglion cell-inner plexiform layer (GCIPL) defects by Cirrus optical coherence tomography (OCT) and examine the spatial relationship between GCIPL defect and visual field (VF) defect patterns. Methods: A total of 116 eyes of 116 normal subjects and 111 eyes of 111 glaucoma patients were included. The 227 study subjects underwent Cirrus OCT imaging in macular cube mode and reliable standard VF testing. Two ophthalmologists blindly classified GCIPL defect patterns and VF defects. The frequency distribution of GCIPL defect patterns and spatial relationships between GCIPL defects and VF defects were investigated. Results: GCIPL defect patterns were classified as minimal, inner, outer, diffuse mild, diffuse severe, inferior confined, inferior dominant, superior confined, and superior dominant defects in normal controls (71.6%, 7.8%, 4.3%, 1.7%, 0%, 10.3%, 1.7%, 1.7%, and 0.9%, respectively) and in glaucoma patients (11.7%, 3.6%, 4.5%, 7.2%, 21.6%, 22.5%, 18.0%, 4.5%, and 6.3%, respectively). In mild and moderate glaucoma patients, the inferior confined type was most frequent (21.9% and 50.0%, respectively). However, the diffuse severe type was most frequent (59.1%) in advanced glaucoma patients. The locations of the VF defects corresponded to the locations of the GCIPL defects in glaucoma patients (P=0.012). Conclusions: Glaucomatous damage of the macula was common and more frequent in the inferior retina. GCIPL defect patterns as determined by SD-OCT imaging corresponded well with central VF defects. It seems macular GCIPL analysis may be useful for evaluating glaucomatous optic neuropathy.